Management of the giant occipital encephaloceles in the neonates. (December 2016) - Ozdemir, Nail; Ozdemir, Senem Alkan; Ozer, Esra Arun
Highlights: Lateral position is considered to be safer than the supine position for endotracheal intubation during surgery, because the weight of the head is not transmitted to the sac; this eliminates the risk of compression-related preoperative rupture of the sac, or an inadvertent incresae in the intracranial pressure. Intraoperative blood and CSF loss, hypothermia, bradycardia and cardiac arrest are most important problems for surgery of giant occipital encephalocele. The size of the encephalocele and the amount of neural tissue found in the sac correlates with the prognosis. Neurological outcome depends upon the presence or absence of hydrocephaly, while intelligence level is mainly related to the absence of brain tissue into the sac. Careful planned and early meticulous surgery results in a satisfactory outcome.